(2x+3)(5x-1)=0

Simple and best practice solution for (2x+3)(5x-1)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x+3)(5x-1)=0 equation:


Simplifying
(2x + 3)(5x + -1) = 0

Reorder the terms:
(3 + 2x)(5x + -1) = 0

Reorder the terms:
(3 + 2x)(-1 + 5x) = 0

Multiply (3 + 2x) * (-1 + 5x)
(3(-1 + 5x) + 2x * (-1 + 5x)) = 0
((-1 * 3 + 5x * 3) + 2x * (-1 + 5x)) = 0
((-3 + 15x) + 2x * (-1 + 5x)) = 0
(-3 + 15x + (-1 * 2x + 5x * 2x)) = 0
(-3 + 15x + (-2x + 10x2)) = 0

Combine like terms: 15x + -2x = 13x
(-3 + 13x + 10x2) = 0

Solving
-3 + 13x + 10x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(-3 + -2x)(1 + -5x) = 0

Subproblem 1

Set the factor '(-3 + -2x)' equal to zero and attempt to solve: Simplifying -3 + -2x = 0 Solving -3 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -2x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -2x = 0 + 3 -2x = 0 + 3 Combine like terms: 0 + 3 = 3 -2x = 3 Divide each side by '-2'. x = -1.5 Simplifying x = -1.5

Subproblem 2

Set the factor '(1 + -5x)' equal to zero and attempt to solve: Simplifying 1 + -5x = 0 Solving 1 + -5x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -5x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -5x = 0 + -1 -5x = 0 + -1 Combine like terms: 0 + -1 = -1 -5x = -1 Divide each side by '-5'. x = 0.2 Simplifying x = 0.2

Solution

x = {-1.5, 0.2}

See similar equations:

| 5(t-2)=t+10 | | 9p+6=3(p+8) | | 4b=6b+-19 | | 4(x+2)=3x+11 | | 3x^2+10+8=0 | | 3p^2-28=27p | | 4(n-1)=n+14 | | 4y^3-3=-12y^2+y | | 10+2z=20 | | -6+x=-10 | | 12t-1=14t-5 | | 8k+10=13k-5 | | 3v^2-7v-20= | | 3a=5a-18 | | 6(x+2)=3(x-5) | | 5x+37=14x-62 | | x^2+5x+18=9 | | 4x+7=x+16 | | 15r+22=97 | | 3(x-4)+5(x+3)=2(3x-5)-6 | | 6(2x-5)=42 | | -4x+2(4-3x)=8-10x | | 9x-21=3+3 | | 3r+12=r+34 | | 4p+8=10p+2 | | -x^2+50x-350=0 | | 8t^2-6t=9 | | x^5-x^4+9x^3-9x^2=0 | | 2x+3=24 | | 5x^2+36x+36=0 | | 6(x-8)-(2x-2)=5x-1 | | .5(20z+18)-8=9(z-3) |

Equations solver categories